2009
DOI: 10.1111/j.1747-4469.2009.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Maybe He's Depressed: Mental Illness as a Mitigating Factor for Drug Offender Accountability

Abstract: Given the often perplexing relationship between mental illness and substance abuse among offenders, this article looks at how a juvenile drug court staff's presumptions of a youth's mental illness affect its decision‐making process. Based on thirteen months of ethnographic fieldwork at a Southern California juvenile drug court, this article uses Manzo and Travers's “law in action” approach to analyze how the staff readjusts its application of normal remedies (a concept developed by Robert Emerson) designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…During the weekly status hearings, the judge adopts an empathetic authority and speaks directly to the client regarding his or her progress in the treatment plan. The defenders and prosecutors, if even present in the court, downplay their professional interests for the purpose of preserving the integrity of the ‘play.’ A handful of other observational studies document how team members respond therapeutically or punitively to perceptions of client non‐compliance in the institutional environs of the problem‐solving courtroom (Castellano 2011; Burns and Peyrot 2008; Paik 2009). Some scholars analyze how specialty court judges, and other team members, employ rhetorical strategies to gain willful compliance from justice‐involved offenders, including metaphorical discourses to encourage struggling offenders and prosecutorial tactics to test their commitment to the program (Burns and Peyrot 2003).…”
Section: Research On Problem‐solving Courtsmentioning
confidence: 99%
“…During the weekly status hearings, the judge adopts an empathetic authority and speaks directly to the client regarding his or her progress in the treatment plan. The defenders and prosecutors, if even present in the court, downplay their professional interests for the purpose of preserving the integrity of the ‘play.’ A handful of other observational studies document how team members respond therapeutically or punitively to perceptions of client non‐compliance in the institutional environs of the problem‐solving courtroom (Castellano 2011; Burns and Peyrot 2008; Paik 2009). Some scholars analyze how specialty court judges, and other team members, employ rhetorical strategies to gain willful compliance from justice‐involved offenders, including metaphorical discourses to encourage struggling offenders and prosecutorial tactics to test their commitment to the program (Burns and Peyrot 2003).…”
Section: Research On Problem‐solving Courtsmentioning
confidence: 99%
“…This finding suggested that correctly diagnosing youth during intake is important, stressing the need for qualified clinical staff who can diagnostically distinguish between substance dependency and substance abuse (Boghosian 2006; Paik 2011). A youth’s mental health state, including later manifestations of mental health issues, was noted as being of great importance for youth staying on track with JDTC programming and ultimately graduating (Fradella et al 2009; Paik 2009). One study noted greater attention and awareness by drug court personnel about mental health issues was needed, particularly for youth with co-occurring disorders, as the youth with co-occurring disorders were less likely to graduate compared to youth who only had a substance abuse issue (Fradella et al 2009; Manchak et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Research designs used in the studies included group comparison with random allocation to conditions (Henggeler et al, 2006); group comparison with matched samples (Applegate & Santana, 2000;Mooney, unpublished;O'Connell, Nestlerode, & Miller, 1999;Rodriguez & Webb, 2004;Searle & Spier, 2006); group comparison without matched samples (Byrnes & Parsons, 1999, Gilmore, Rodriguez, & Webb, 2005Polakowski, Hartley, & Bates, 2008;Shaw & Robinson, 1998;Weisz et al, 2002); comparison of a single sample at different periods (Behnken, Arredondo, & Packman, 2009); retrospective group comparison (Sloan, Smylka, & Rush, 2004); follow-up studies with no comparison group (Carswell, 2004;Eardley et al, 2004;Ruiz, Stevens, Fuhriman, Bogart, & Korchmaros, 2009); regression analysis (Halliday-Boykins et al, 2010); financial cost analysis (McCollister, French, Sheidow, Henggeler, & HallidayBoykins, 2007;Vick, 2006); focus groups or interviews (Bryan, Hiller, & Leukefeld, 2006;Eardley et al, 2004;Gilmore et al, 2005;Paik, 2009;Searle & Spier, 2006;Whiteacre, 2004); ethnography (Paik, 2009); and a case study (Arredondo et al, 2001). (Sloan & Smylka, 2003;Weisz et al, 2002); and social or psychological assessments or screening tools (Carswell, 2004;Gilmore et al, 2005;Mooney, unpublished;...…”
Section: Research Designsmentioning
confidence: 98%
“…(Sloan & Smylka, 2003;Weisz et al, 2002); and social or psychological assessments or screening tools (Carswell, 2004;Gilmore et al, 2005;Mooney, unpublished;Ruiz et al, 2009). Qualitative data was collected through stakeholder interviews or focus groups (Bryan et al, 2006;Eardley et al, 2004;Gilmore et al, 2005;Paik, 2009;Searle & Spier, 2006;Whiteacre, 2004) and observations of court processes (Carswell, 2004;Eardley et al, 2004;Paik, 2009;Whiteacre, 2004).…”
Section: Research Designsmentioning
confidence: 99%
See 1 more Smart Citation